Infants < 90 days of age with late-onset sepsis display disturbances of the microbiome-immunity interplay. - Graspeuntner, Simon; Lupatsii, Mariia; van Zandbergen, Vera; Dammann, Marie-Theres; Pagel, Julia; Nguyen, Duc Ninh; Humberg, Alexander; Göpel, Wolfgang; Herting, Egbert; Rupp, Jan; Härtel, Christoph; Fortmann, Ingmar (Infection, 2025)
Objective: We hypothesized that previously healthy infants < 90 days of age with late-onset sepsis (LOS) have disturbances of the gut microbiome with yet undefined specific immunological patterns. Methods: We performed a prospective single-center convenience sample study between January 2019 and July 2021 in a case-control design. Routine diagnostics included conventional cultures (blood, cerebrospinal fluid, urine), PCRs and inflammatory markers in infants aged < 90 days with clinical LOS. We additionally analyzed blood lymphocyte subsets including CD4 + CD25 + forkhead box protein (FoxP3)+ Tregs and performed 16 S rRNA sequencing of stool samples, both compared to age-matched healthy controls. Results were adjusted for potential confounders that may influence microbial composition. Results: 51 infants with fever and clinical LOS were enrolled. Bacterial sepsis was diagnosed in n = 24 (47.1%) and viral infection in n = 13 (25.5%) infants, whereas in 14 (27.3%) infants the cause of fever remained undetermined. When compared to healthy controls, the gut microbiome of LOS infants at disease onset was characterized by a shift in community composition, specifically, decreased abundance of B. longum and an increase of Bacteroidia spp. Intriguingly, the abundance of B. longum negatively correlated with the frequency of blood CD4-positive cells in healthy controls but not in infants with LOS. At one year of age, we observed microbiome differences in infants with history of LOS when compared to healthy controls, such as an increased gut microbial diversity. Conclusion: Our data suggest potential signatures of the microbiome-immunity interplay in infants with LOS, which should be investigated further as possible targets for prevention.